2005
DOI: 10.1245/aso.2005.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Rate as a Predictor of Sentinel Lymph NodePositivity in Patients With Thin Melanomas

Abstract: In patients with thin melanomas, MR >0 seems to be a significant predictor of SLN positivity that may be used to risk-stratify and select patients for LM/SL. To confirm these results, the predictive value of MR for SLN positivity needs to be validated in other populations of thin-melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
124
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(152 citation statements)
references
References 32 publications
22
124
2
3
Order By: Relevance
“…A large number of studies have tried to identify the criteria that may be used to indicate SLNB in thin melanomas, with conflicting results. Most of them were conducted on short retrospective heterogeneous cohorts [11,18,20,40,41]. In our study, we were not able to identify criteria associated with SLN metastasis in the subpopulation of patients with melanoma <1 mm.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A large number of studies have tried to identify the criteria that may be used to indicate SLNB in thin melanomas, with conflicting results. Most of them were conducted on short retrospective heterogeneous cohorts [11,18,20,40,41]. In our study, we were not able to identify criteria associated with SLN metastasis in the subpopulation of patients with melanoma <1 mm.…”
Section: Discussionmentioning
confidence: 73%
“…The present AJCC staging classification recommends the use of mitotic rate as a prognostic factor (T1a vs. T1b). It has previously been reported that the risk of SLN metastasis is increased in case of a mitotic index >1 [18,20,39]. This may have influenced our results.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The guidelines in regard to Breslow thickness, taking in mind where SLNB staging benefits do not outweigh the risks of the procedure, are constantly reviewed and modified. Factors associated with increased incidence of positive SLNs in melanoma patients have been thoroughly studied and reported in the literature and include tumor thickness [5]- [24], ulceration [16]- [22], mitotic rate [7] [14] reported positive SLN in the ≤0.75 mm group (group A), ranging from 1.7% to 6% (Table 4). In our study (Table 1) in the 0.76 -1.00 mm group (group B) the percentage of positive SLNs was 11.1%, whereas in the above-mentioned studies [5]- [14] it was ranging from 3.9% to 12.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The variation of selection criteria among published retrospective studies with small patient populations makes comparisons difficult [4][5][6][7]. Factors reported to be predictive of SLN positivity include Breslow thickness, ulceration, mitotic rate, Clark level, lymphovascular invasion, age, melanoma subtype, and tumor location [8][9][10][11][12][13][14]. Some studies have identified no predictive parameters [15][16][17][18].…”
Section: Prognostic Factorsmentioning
confidence: 99%